2006
DOI: 10.1111/j.1442-2042.2006.01351.x
|View full text |Cite
|
Sign up to set email alerts
|

Bladder reconstruction using a collagen patch prefabricated within the omentum

Abstract: Objective: We present our experience with a novel bladder reconstruction model using a collagen sponge pre-embedded within the omentum. The aim of the study is to evaluate tissue regeneration of the reconstructed bladder and the effect of prefabricating the collagen patch within the omentum. Materials and methods: Twenty pigs were divided into three groups. For the prefabricated patch group (PFP; n = 10), collagen sponge was inserted into the omentum. After 1 week, the pigs underwent a hemicystectomy and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
(9 reference statements)
1
11
1
3
Order By: Relevance
“…Although regeneration of smooth muscle-like tissue is usually observed in BAM, SIS, or other collagen-derived materials, their morphology and function is not completely equivalent to a native bladder detrusor. 15,26,36 The origin of regenerated smooth muscle may be de-differentiated smooth muscle cells from adjacent bladder parenchyma, while a minor contribution of bone marrow cells was also reported by our group. 19,37 Initially, urothelial cells were believed to promote muscle regeneration via epithelialmesenchymal interaction, 19 but a study by our group demonstrated that the growth factor milieu created by urothelium, with higher levels of basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF), had a negative effect on muscle maturation.…”
Section: Vascularity and Smooth Muscle Regeneration: Two Major Barriementioning
confidence: 74%
“…Although regeneration of smooth muscle-like tissue is usually observed in BAM, SIS, or other collagen-derived materials, their morphology and function is not completely equivalent to a native bladder detrusor. 15,26,36 The origin of regenerated smooth muscle may be de-differentiated smooth muscle cells from adjacent bladder parenchyma, while a minor contribution of bone marrow cells was also reported by our group. 19,37 Initially, urothelial cells were believed to promote muscle regeneration via epithelialmesenchymal interaction, 19 but a study by our group demonstrated that the growth factor milieu created by urothelium, with higher levels of basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF), had a negative effect on muscle maturation.…”
Section: Vascularity and Smooth Muscle Regeneration: Two Major Barriementioning
confidence: 74%
“…Others have successfully exploited the omentum for the vascularization of hepatic tissues and for bladder construction (30,31). Recently, our group transplanted cardiac cell-seeded scaffolds into the peritoneal cavity in an attempt to induce tissue engineering of the patch (32).…”
Section: Scar) (A and B) Nonpaced (Spontaneous) Electrical Signals Rmentioning
confidence: 99%
“…[1][2]16 Among the natural polymers, collagen has been widely used for bladder tissue engineering applications because of its favorable cell-matrix interactions. [16][17][18][19] However, conventional collagen-based scaffolds in the form of hydrogels that allow rapid introduction of cells or tissues suffer from low mechanical strength and are not conducive to surgical handling. To overcome this limitation, the technique of plastic compression of collagen hydrogels was introduced by Brown et al 20 While this approach improves the mechanical properties, it does not provide sufficient strength for bladder engineering.…”
Section: Introductionmentioning
confidence: 99%